42.6k views
2 votes
How do i solve this using elimination

How do i solve this using elimination-example-1
User Nojhan
by
5.2k points

2 Answers

5 votes

Answer:

(6, 4 )

Explanation:

Given the 2 equations

4x - 3y = 12 → (1)

x + 2y = 14 → (2)

Multiplying (2) by - 4 and adding to (1) will eliminate the y- term

- 4x - 8y = - 56 → (3)

Add (1) and (3) term by term

(4x - 4x) + (- 3y - 8y) = (12 - 56) ← simplify

- 11y = - 44 ( divide both sides by - 11 )

y = 4

Substitute y = 4 into either (1) or (2)

(2 ) : x + 8 = 14 ( subtract 8 from both sides )

x = 6

Solution is (6, 4 )

User Siddharth Prajosh
by
5.8k points
5 votes

Answer:

The value of x=6 and y=4.

How do i solve this using elimination-example-1
User Acrespo
by
5.5k points